Torrens and Customary Land Tenure: a Case Study of the Land Titles Registration Act 2008 of Samoa - Ye, Ruiping (Victoria University of Wellington Law Review, 2009)
This article describes the customary land tenure in Samoa, and analyses the effects of the introduction of a Torrens system of land registration on the customary land tenure. In particular, it examines the registration of adjudicated customary land (customary land in respect of which judgment has been made by the Land and Titles Court) under the Land Titles Registration Act 2008, as well as the combined effect of the Taking of Land Act 1964 and Torrens registration on customary land. It argues that the LTRA 2008 may be repugnant to the Constitution and that the Torrens system is incompatible with customary land tenure. It recommends that the law expressly exclude customary land from the indefeasibility of title effect of the Torrens system.